Phosphate Metabolism in Intact Human Erythrocytes: Determination by Phosphorus-31 Nuclear Magnetic Resonance Spectroscopy - Henderson, Thomas O. (1974)
Whole human blood was examined by (31)P nuclear magnetic resonance spectroscopy. Individual phosphates (α,β,γ) of ATP were identifiable, and two microenvironments appeared to be present for this molecule. When sequential recordings of freshly collected blood were made, 2,3-diphosphoglycerate was observed to decrease in association with a concomitant increase in inorganic orthophosphate. When aged cells containing little 2,3-diphosphoglycerate were incubated in the presence of inosine and pyruvate, 2,3-diphosphoglycerate formation could be demonstrated. These results show that cellular metabolism can be recorded directly in intact cells by (31)P nuclear magnetic resonance.